THE EVOLUTION AND IMPACT OF THE NORTH AMERICAN FREE TRADE AGREEMENT (NAFTA) ON THE ECONOMIC DEVELOPMENT OF THE MEMBER COUNTRIES - ZAHORODNIA, Alona (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the formation, functioning, and impact of the North American Free Trade Agreement (NAFTA) on the economies of the member countries – the United States, Canada, and Mexico. The study explores the historical background of the agreement’s formation, its main objectives, implementation mechanisms, and key principles governing trade relations among the participating states. The author evaluates the economic effects of NAFTA, including its influence on international trade volumes, foreign direct investment attraction, shifts in the competitive positions of member countries, the development of production supply chains, and employment growth. The socio-economic consequences of the agreement’s implementation are also examined, such as changes in labor market structures, the overall standard of living, and the development of key economic sectors. The paper assesses both the advantages and disadvantages of the agreement, its role in global trade processes, and the challenges NAFTA faced due to global economic transformations, external shocks, and political changes in the member countries. Special attention is given to the modernization of the agreement and its transition into the new United States-Mexico-Canada Agreement (USMCA), which came into effect in 2020. The article analyzes the key differences between NAFTA and USMCA, highlighting regulatory changes in areas such as rules of origin, labor market access conditions, digital trade, and intellectual property protection. It also explores how the new provisions of the agreement affect economic dynamics in the region, enhance business competitiveness, and adapt trade policies to modern globalization challenges. The author concludes with insights into the prospects for further regional integration and the potential consequences of USMCA’s implementation for the economies of the member countries. Additionally, the paper assesses the possible risks and opportunities for businesses operating under the updated trade framework.